Four layers reconstruction of the posterior ear canal wall in one stage surgery - Mokbel Khalefa, Khaled M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Canal wall down mastoidectomy are still practiced in cases of chronic suppurative otitis media with cholesteatoma to ensure complete disease removal. The resulting cavity is prone to recurrent infection, chronic discharge and frequent care. Reconstruction of the posterior canal wall should be planned by the surgeon. Various techniques for external auditory canal (EAC) reconstruction have been recommended to eliminate open cavity problems. The surgeon should choose the type of grafts either autologous, homografts or synthetic materials. Furthermore, the surgeon should decide whether to do the reconstruction either immediate in the first stage of surgery or delayed as a second stage. Methods: In this study, the ridge was reconstructed at the same time of mastoidectomy by autologous tissues. The presenting study reconstructed the posterior canal wall in four layers; skin, perichondrial flap, cartilage and periosteal flap in that order from the meatal side to the mastoid side. The presenting study included 48 patients (32 males and 16 females) with age ranged from 18-55 and 20-50 years. All included patients were presented at the outpatient clinic with unilateral chronic suppurative otitis media with persistent discharge. They had been operated at our tertiary hospital between January. 2012 to March 2014. Results: Successful reconstruction was obtained in all cases, with no dehiscence or necrosis. Conclusions: The reconstruction of the posterior wall by the four layers technique was successful and efficient. It is recommended to do this repair concomitantly with canal wall down mastoidectomy as one stage surgery.